Evaluation of the nitrate and nitrite content of vegetables commonly grown in Slovenia - Kmecl, Veronika; Knap, Tea; Žnidarčič, Dragan (Italian Journal of Agronomy, 2017)
Nitrate (NO3–) and nitrite (NO2–) levels of a total 1195 samples of nine different vegetables (lettuce, potato, cabbage, carrot, string beans, tomato, cucumber, cauliflower and pepper) collected at several locations of an intensive agricultural area in Slovenia were analysed during a period of 13 years. The content of NO2– and NO3– ions in commercial mature samples was determined using a segmented flow analyser. The average NO3– content was the highest in lettuce (962 mg/kg), cabbage (795 mg/kg), string beans (298 mg/kg), carrot (264 mg/kg), cauliflower (231 mg/kg), potato (169 mg/kg) and was moderately high in cucumber (93 mg/kg) and pepper (69 mg/kg). A low NO3– content was found in tomato (2– did not exceed 0.5 mg/kg, with the exception of potato (1.08 mg/kg). Six samples of lettuce exceeded the maximum permissible level of NO3– according to current European Union (EU) legislation. Based on the results of our investigation, we assessed the approximate daily intake (DI) of NO3– and NO2– to human body. The results indicated that with the consumption of potato, the daily intake per inhabitant is close to the acceptable DI permitted in EU.